Forma Narrativa como um Instrumento Cognitivo - Mink, Louis; Ohara, João (Revista de Teoria da História, 2024)
Tradução de: MINK, Louis O. Narrative Form as a Cognitive Instrument. In: CANARY, Robert e KOZICKI, Henry (eds.). The Writing of History: Literary Form and Historical Understanding. Madison: University of Wisconsin Press, 1978, p. 129-149. From The Writing of History: Literary Form and Historical Understanding, edited by Robert H. Canary and Henry Kozicki. Reprinted by permission of the University of Wisconsin Press. © 1978 by the Board of Regents of the University of Wisconsin System. All rights reserved.